A Comparative Study to Evaluate the Amount of Adhesive remnant on the teeth after the removal of orthodontic brackets which have been polymerized with LED curing units. In- vitro Study - العبدالرزاق فخر; عبد الكريم حسن (Latakia University Journal -Medical Sciences Series, 2023)
Aim: the purpose of this study was to compare the adhesive remnant index of orthodontic metallic brackets photo-activated with High Intensity light emitting diode(LED) and Traditional light emitting diode on brackets bonding at different exposure times. Material and Methods: A light-curing adhesive paste Light Bond ®,Resiliance Orthodontic Products,Inc.USA) ) was used to bond brackets using different curing times. Sixty human permanent bicuspid extracted for orthodontic purposes were obtained and randomly divided into 3 groups (n=20). The first group was bonded using a conventional light-emitting diode (LED) (1200 mW/cm2) for 20 seconds, which served as a control group. The other two groups were bonded with a high-intensive light-emitting diode LED (3200 mW/cm2) for 6 and 2 seconds ,respectively. After storage in distilled water for 24 h, a universal testing machine was used to apply an occlusal shear force directly to the enamel-bracket interface at a speed of 0.5 mm/minute. The Adhesive Remnant Index (ARI) was assigned at fractured specimens. Results: Mean results and standard deviations for the groups were: group I (20s) = 19.8 MPa ,group II (6s)= 15.2 MPa , group III (2s) = 12.2 MPa. One-way analysis of variance detected statistically significant differences in bond strength between group I and group II (P=0.029). And between group I and group III (P=0.001).but no significant difference was observed in the bond strengths between group II and group III (P=0.153). Chi-square analysis also detected differences in the adhesive remnant scores. Conclusions: Reducing exposure time significantly decreased mean values of SBS, even with the use of a high-power LED unit. Reduction in time also affect the amount of adhesive remnant,(less exposure time more adhesive remnant).